The Louisiana Populist Movement, 1881-1900 - Barnes, Donna A., 1954- (Book collections on Project MUSE., 2011)
The Populist movement of the late nineteenth century represents one of the largest third-party challenges in American history. Throughout the South widespread drops in crop prices led to agrarian revolt, which contributed to the movement's popularity. Yet, in the largely rural state of Louisiana, despite the political group's focus on empowering distressed farmers, this challenge proved far less successful. In Donna A. Barnes's The Louisiana Populist Movement the question of ineffectuality makes an intriguing political case study of the Pelican State and Populism. Emerging in the 1890s as the.